High rate of seropositivity of Chlamydia pneumoniae IgA in male patients with nonalcoholic steatohepatitis - Bolukbas, FF; Bolukbas, C; Zeyrek, F; Aslan, M; Bahcecioglu, HI; Ozardali, I (Springer, 2005)
The aim of this study was to investigate if there was any relationship between nonalcoholic steatohepatitis and the rate of Chlamydia pneumoniae seropositivity in a male population. Fifteen men with nonalcoholic steatohepatitis and 20 healthy men were enrolled in the study. The seropositivity rate of Chlamydia pneumoniae immunoglobulin A in the nonalcoholic steatohepatitis and control groups was 53.3 and 5%, respectively. The rate of Chlamydia pneumonia immunoglobulin A positivity was significantly higher in the nonalcoholic steatohepatitis group than the controls (P=0.002), while such a difference did not occur for Chlamydia pneumoniae immunoglobulin G positivity (P>0.05). There is an association between nonalcoholic steatohepatitis and persistent Chlamydia pneumoniae infection as a probable causative or triggering agent. These findings suggest that further studies are necessary to clarify this association.
Keywords: Chlamydia pneumoniae; antibody IgA; nonalcoholic steatohepatitis; serology; male